Abstract surrealism: the New York Schoolers’ ‘Personalized Surrealism’ - Ekin Erkan (Journal of Aesthetics & Culture)
Drawing from New York School artists’ witness accounts, correspondence, and archival records from lesser-consulted New York gallery archives (e.g. Hugo Gallery, Iolas Gallery, etc.), this paper challenges recent retellings that abdicate witness accounts in general and abrogate Roberto Matta’s influence on the New York School in particular. This paper’s thesis is that Matta’s influence on the nascent New York School American artists in the early-to-mid 1940s gave critical shape to the constituent American artists’ conception of automatism and refined the ambit of their project. I begin by situating Matta’s conception of automatism vis-à-vis the art historical semblance of Duchamp’s and Breton. Looking at a range of archival material hitherto unconsidered in the extant literature, I then expound on the New York School’s reception of key confluences/events, including: Gordon Onslow Ford’s lecture at the New School of Social Research on 5 March 1941, which many New York School artists attended and where Matta’s work was underscored as spearheading a novel approach to Surrealist automatism; the six Fall-Winter 1942–43 collaborative automatist studio sessions that Matta led with Jackson Pollock, Gerome Kamrowski, Peter Busa, Robert Motherwell, and William Baziotes; and witness accounts on Matta’s institutional support of the Americans’.